An Unusual Cause of Neonatal HIP Dislocation: Infantile Myofibromatosis Presenting as Developmental Dysplasia of the HIP. Issue 5 (September 2016) - Woo, Timothy; Win, Thuzar
Introduction: Infantile myofibromatosis (IM) is a rare paediatric fibrous tumour also known as a desmoid tumour that occurs in around 1:150000 live births. It manifests as solitary or multicentric fibrous masses in the musculoaponeurotic soft tissues and can affect the visceral organs and bones. Case discussion: We report a case of infantile myofibromatosis of the gluteus maximus muscle in an 18-day old neonate presenting atypically as a case of developmental dysplasia of the hip due to local involvement of the sciatic nerve. However, failure of improvement with conventional management and clinical wasting of the lower leg muscles was indicative of a secondary cause of the patient's hip dislocation, which was confirmed on imaging and surgical biopsy. Discussion: This case report aims to emphasise the importance of considering secondary causes of neonatal hip dislocation, especially in cases where imaging findings are atypical of conventional DDH. Although imaging appearances on ultrasound and CT may vary, the signal characteristics and enhancement pattern of soft tissue myofibromata on MRI with and without gadolinium contrast appear to be the most consistent finding in these cases.